Management of Recurrent Aphthous Stomatitis (RAS) Cases Through a Communication, Information, and Education Approach - Diah Rochmayani Tri Lestari; Naviatullaily Naviatullaily (Paspama Institute, 2026)
Recurrent Aphthous Stomatitis (RAS) is an inflammatory condition of the oral mucosa characterized by recurrent ulcers typically presenting with a yellowish-white base and erythematous borders. These lesions are often painful and may interfere with daily activities. The exact cause of RAS is unknown, although predisposing factors include hormonal disturbances, nutritional deficiencies, and stress. To evaluate the management of Recurrent Aphthous Stomatitis (RAS) caused by hormonal imbalance, nutritional deficiencies, and stress using the Communication, Information, and Education. A 28-year-old woman presented with recurrent canker sores on the right buccal mucosa and the commissure of the upper lip for the past three days. The patient experienced similar complaints every month before menstruation. Intraoral examination revealed two irregular ulcerative lesions, measuring less than 1 cm in size, exhibiting a yellowish-withe base with erythematous border. The diagnosis was established as multiple minor Recurrent Aphthous stomatitis lesions. Through a CIE approach, the patient was educated regarding the mechanisms of RAS, including the role of hormonal changes during the luteal phase, the impact of stress through activation of the HPA axis, and the importance of nutrients such as vitamin B12, folate, and iron in mucosal regeneration. The patient was advised to improve dietary habits, avoid irritant foods, maintain good oral hygiene, manage stress, and ensure adequate hydration. Referral to an obstetrician-gynecologist or nutritionist was recommended when indicated Oral therapy was provided in the form of a multivitamin containing vitamins A, B-complex, C, D, and E, along with minerals. The patient was instructed to take one tablet tablet once daily for 10 days to help improve nutritional status and promote ulcer healin. The management of RAS requires a holistic approach through effective communication, information, and education (CIE) regarding trigger factors and the underlying mechanisms of RAS, combined with supportive therapy and lifestyle modification to prevent recurrence.